Impaired neutrophil-mediated cell death drives Ewing’s Sarcoma in the background of Down syndrome - Peirone, Serena; Tirtei, Elisa; Campello, Anna; Parlato, Caterina; Guarrera, Simonetta; Mareschi, Katia; Marini, Elena; Asaftei, Sebastian Dorin; Bertero, Luca; Papotti, Mauro; Priante, Francesca; Perrone, Sarah; et al. (Frontiers in Oncology, 2024)
IntroductionEwing Sarcoma (EWS) has been reported in seven children with Down syndrome (DS). To date, a detailed assessment of this solid tumour in DS patients is yet to be made.MethodsHere, we characterise a chemo-resistant mediastinal EWS in a 2-year-old DS child, the youngest ever reported case, by exploiting sequencing approaches.ResultsThe tumour showed a neuroectodermal development driven by the EWSR1-FLI1 fusion. The inherited myeloperoxidase deficiency of the patient caused failure of neutrophil-mediated cell death and promoted genomic instability.DiscussionIn this context, the tumour underwent genome-wide near haploidisation resulting in a massive overexpression of pro-inflammatory cytokines. Recruitment of defective neutrophils fostered rapid evolution of this EWS.